Perception of Telemedicine and Digital Healthcare in Kathmandu Valley - Shrestha, Raji (International Journal of Atharva, 2026)
Background: Telemedicine and digital medicine have been developed as revolutionary tools for improving access to healthcare facilities especially in areas where there is geographic and infrastructural difficulty. Nepal stands at a unique position with respect to the delivery of health care services due to its challenging geography and rural environment. Despite efforts by the Nepalese government to develop the Digital Nepal Strategy (2019), inconsistency prevails regarding telemedicine applications.Methods: A descriptive cross-sectional research design was adopted through an online survey conducted on 206 Nepalese citizens aged 18 and above. The data were collected from a structured questionnaire assessing awareness, perceptions related to environmental sustainability, accessibility, trust, and telemedicine. Analysis of the results was done through SPSS.Results: Most participants belonged to the age group 18-25 (52.9%), while males made up 51.9% and females 48.1%. There were more urban respondents, making 56.8% of all participants. Awareness level was found significantly higher than neutral point (M=3.46, t=7.640, p